Središnja etapa demografske tranzicije : stanovništvo Babina Polja na otoku Mljetu (1870-1880) - Mihović, Nela (Array, 2009)
The demographic picture of the parish of Babino Polje correlates closely with that of the Dubrovnik region, exhibiting all the specific features of an island community. Babino Polje demonstrates a host of atypical characteristics which are the product of the economic conditions and geographical isolation. All demographic indicators show that in the period 1870-1880, Babino Polje was already affected by transition.